2018
DOI: 10.1093/bjc/azy015
|View full text |Cite
|
Sign up to set email alerts
|

Putting the ‘Street’ in Gang: Place and Space in the Organization of Scotland’s Drug-Selling Gangs

Abstract: Street gangs, by definition, enjoy a special relationship with the street. Prior research shows that some communities are synonymous with gangs and that turf holds a combination of expressive and instrumental value for gang members. As gangs evolve over time and through different levels of organization, however, gangs' relationship with the street changes. This shifting street dynamic is underexplored in prior research, thus, drawing on qualitative data from Scotland and Bourdieu's theory of social field, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 54 publications
(57 reference statements)
1
21
0
6
Order By: Relevance
“…To this end, McLean, have shed light on the hidden role of street gangs in drug distribution in Scotland. Following similar trends observed in London (e.g., Densley, 2014;Harding, 2014), McLean et al found that gangs have evolved to not necessarily control drug markets, but to participate in them and benefit from territorial control of a marketplace (see also, McLean, 2018;McLean, Deuchar, Harding, & Densley, 2018). The authors likewise note that while the term 'gang' is often applied in a stereotypical manner by those in the political establishment and media as representing a cohesive criminal group (Deuchar, 2009, Deuchar, 2016, in reality there are significant variations between gangs in regard to hierarchy, division of labour, cohesion, and purpose (Densley, 2012).…”
Section: Literature Reviewmentioning
confidence: 70%
“…To this end, McLean, have shed light on the hidden role of street gangs in drug distribution in Scotland. Following similar trends observed in London (e.g., Densley, 2014;Harding, 2014), McLean et al found that gangs have evolved to not necessarily control drug markets, but to participate in them and benefit from territorial control of a marketplace (see also, McLean, 2018;McLean, Deuchar, Harding, & Densley, 2018). The authors likewise note that while the term 'gang' is often applied in a stereotypical manner by those in the political establishment and media as representing a cohesive criminal group (Deuchar, 2009, Deuchar, 2016, in reality there are significant variations between gangs in regard to hierarchy, division of labour, cohesion, and purpose (Densley, 2012).…”
Section: Literature Reviewmentioning
confidence: 70%
“…In the United Kingdom, Campana and Varese () found that most OC activities were conducted in the absence of governance‐type OC, but illegal governance did still exist; a finding consistent with other studies in high‐crime areas in Britain, including London (Densley ) and Glasgow (McLean et al . ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Hence why initial discussions on UK gangs frequently commence by citing interesting vignettes of early Twentieth Century social life (Downes, 1966) that speak of homogenous white working-class communities (not modern British multiculturalism); of class control and deference (not the fluidity of identity and status); of state intervention (not state absenteeism); of structured employment (not the gigeconomy); and of a baronial press monopoly on news creation (not user-generated and publicmediated information). Such is a world quite distant from the "glocal" violent street worlds of today (van Hellemont and , where the boundaries between gangs and organised crime are blurred (McLean et al, 2019), criminal groups use smart phones and social media (e.g., Storrod and Densley, 2017), and gangs venture into exploitative county lines drug dealing outside of traditional territorial boundaries (e.g., Coomber and Moyle, 2018;McLean et al, 2020;Robinson et al, 2019).…”
Section: Shift Happens: the Perils And Pitfalls Of Studying Uk Gangsmentioning
confidence: 99%